Acinetobacter spp. Infections in Malaysia: A Review of Antimicrobial Resistance Trends, Mechanisms and Epidemiology - Mohd. Rani, Farahiyah; A. Rahman, Nor Iza; Ismail, Salwani; Alattraqchi, Ahmed Ghazi; Cleary, David W.; Clarke, Stuart C.; Yeo, Chew Chieng (Frontiers in Microbiology, 2017)
Acinetobacter spp. are important nosocomial pathogens, in particular the Acinetobacter baumannii-calcoaceticus complex, which have become a global public health threat due to increasing resistance to carbapenems and almost all other antimicrobial compounds. High rates of resistance have been reported among countries in Southeast Asia, including Malaysia. In this review, we examine the antimicrobial resistance profiles of Acinetobacter spp. hospital isolates from Malaysia over a period of nearly three decades (1987 – 2016) with data obtained from various peer-reviewed publications as well as the Malaysian National Surveillance on Antibiotic Resistance (NSAR). NSAR data indicated that for most antimicrobial compounds, including carbapenems, the peak resistance rates were reached around 2008 – 2009 and thereafter, rates have remained fairly constant (e.g., 50 – 60% for carbapenems). Individual reports from various hospitals in Peninsular Malaysia do not always reflect the nationwide resistance rates and often showed higher rates of resistance. We also reviewed the epidemiology and mechanisms of resistance that have been investigated in Malaysian Acinetobacter spp. isolates, particularly carbapenem resistance and found that blaOXA-23 is the most prevalent acquired carbapenemase-encoding gene. From the very few published reports and whole genome sequences that are available, most of the Acinetobacter spp. isolates from Malaysia belonged to the Global Clone 2 (GC2) CC92 group with ST195 being the predominant sequence type. The quality of data and analysis in the national surveillance reports could be improved and more molecular epidemiology and genomics studies need to be carried out for further in-depth understanding of Malaysian Acinetobacter spp. isolates.